2022
DOI: 10.3390/ijerph191610337
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Risk Environment Impact Analysis and Complexity Assessment of Autonomous Vehicles Based on the Potential Field Method

Abstract: Although autonomous vehicles have introduced a promising potential for improving traffic safety and efficiency, ensuring the safety of autonomous vehicles in complex road traffic environments is still a huge challenge to be tackled. To quickly quantify the potential risk factors of autonomous vehicles in traffic environments, this paper focuses mainly on the influence of the depth and breadth of the environment elements on the autonomous driving system, uses the potential field theory to establish a model of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The results showed that the road segment type is the main factor affecting static complexity, and finally, the test scenarios with high total complexity were selected to evaluate the safety performance of autonomous vehicles. In the study of risk factors analysis for autonomous vehicles [23], Cheng et al calculated the complexity of static scenes at intersections using the AHP method. The interaction with traffic signals was considered to be the most important factor.…”
Section: Analytic Hierarchy Process Methodsmentioning
confidence: 99%
“…The results showed that the road segment type is the main factor affecting static complexity, and finally, the test scenarios with high total complexity were selected to evaluate the safety performance of autonomous vehicles. In the study of risk factors analysis for autonomous vehicles [23], Cheng et al calculated the complexity of static scenes at intersections using the AHP method. The interaction with traffic signals was considered to be the most important factor.…”
Section: Analytic Hierarchy Process Methodsmentioning
confidence: 99%
“…Wang et al [ 45 ], on the other hand, proposed three different fields (moving objects, road environment, and driver characteristics). Similarly, Cheng et al [ 46 ] based their environmental complexity evaluation model on the potential field theory. The environment elements are represented by a positive point charge or uniformly charged wires that create a potential field in their vicinity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The comprises stationary elements of the environment, such as road segments, tunnels, signage, road markings, vegetation, etc., whereas the encompasses dynamic elements such as vulnerable road users, vehicles, and non-motorized vehicles. To calculate the for , we adopt the equation from the study conducted by Cheng et al [ 27 ]. This equation combines the complexity of both static and dynamic elements, and the result gives the overall complexity of the traffic environment.…”
Section: Collaborative Convoy Driving—a Coalitional Gamementioning
confidence: 99%
“…To calculate the for , we adopt the equation from the study conducted by Cheng et al [ 27 ]. This equation combines the complexity of both static and dynamic elements, and the result gives the overall complexity of the traffic environment.…”
Section: Collaborative Convoy Driving—a Coalitional Gamementioning
confidence: 99%